3 val (r1s, f1s) = simp(r1) |
3 val (r1s, f1s) = simp(r1) |
4 val (r2s, f2s) = simp(r2) |
4 val (r2s, f2s) = simp(r2) |
5 (r1s, r2s) match { |
5 (r1s, r2s) match { |
6 case (ZERO, _) => (ZERO, F_ERROR) |
6 case (ZERO, _) => (ZERO, F_ERROR) |
7 case (_, ZERO) => (ZERO, F_ERROR) |
7 case (_, ZERO) => (ZERO, F_ERROR) |
8 case (ONE, _) => (r2s, F_SEQ_Void1(f1s, f2s)) |
8 case (ONE, _) => (r2s, F_SEQ_Empty1(f1s, f2s)) |
9 case (_, ONE) => (r1s, F_SEQ_Void2(f1s, f2s)) |
9 case (_, ONE) => (r1s, F_SEQ_Empty2(f1s, f2s)) |
10 case _ => (SEQ(r1s,r2s), F_SEQ(f1s, f2s)) |
10 case _ => (SEQ(r1s,r2s), F_SEQ(f1s, f2s)) |
11 } |
11 } |
12 } |
12 } |
13 ... |
13 ...} |
14 |
14 def F_SEQ_Empty1(f1: Val => Val, f2: Val => Val) = |
15 def F_SEQ_Void1(f1: Val => Val, f2: Val => Val) = |
15 (v:Val) => Sequ(f1(Empty), f2(v)) |
16 (v:Val) => Sequ(f1(Void), f2(v)) |
16 def F_SEQ_Empty2(f1: Val => Val, f2: Val => Val) = |
17 def F_SEQ_Void2(f1: Val => Val, f2: Val => Val) = |
17 (v:Val) => Sequ(f1(v), f2(Empty)) |
18 (v:Val) => Sequ(f1(v), f2(Void)) |
|
19 def F_SEQ(f1: Val => Val, f2: Val => Val) = |
18 def F_SEQ(f1: Val => Val, f2: Val => Val) = |
20 (v:Val) => v match { |
19 (v:Val) => v match { |
21 case Sequ(v1, v2) => Sequ(f1(v1), f2(v2)) } |
20 case Sequ(v1, v2) => Sequ(f1(v1), f2(v2)) } |